2015
DOI: 10.1111/joor.12333
|View full text |Cite
|
Sign up to set email alerts
|

Pain and problems: a prospective cross‐sectional study of the impact of dental emergencies

Abstract: One-third of the population will only attend the dentist for an acute problem, often waiting a period of time before presenting. The objective of this study was to investigate the levels of pain in patients presenting for a dental emergency and the impact this had on their quality of life. Questionnaires were provided to adult patients attending dental emergency services over 1 week. Demographic and clinical details were collected. Quality of life was measured using EQ-5D-5L. Pain and the interference it cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
42
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 12 publications
10
42
3
4
Order By: Relevance
“…This demographic is in keeping with previous studies carried out in the United States (9,13-25), Canada (26,27), Australia (28) and Korea (29). Interestingly, it is also this demographic who are known not to attend a dentist on a regular basis, and instead opt for emergency dental treatment (4,(30)(31)(32)(33)(34). The reason for the gender differences observed is unknown, however, but may relate to the nature of the diagnoses (e.g.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This demographic is in keeping with previous studies carried out in the United States (9,13-25), Canada (26,27), Australia (28) and Korea (29). Interestingly, it is also this demographic who are known not to attend a dentist on a regular basis, and instead opt for emergency dental treatment (4,(30)(31)(32)(33)(34). The reason for the gender differences observed is unknown, however, but may relate to the nature of the diagnoses (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…Almost one‐third of the adult population of the UK will only seek dental care when they are having an acute problem, and 9% of the population experience ongoing dental pain . Those seeking emergency dental care may seek care from other healthcare professionals such as general medical practitioners (GPs) , pharmacists , secondary care dental emergency clinics and medical emergency departments (MED) rather than attending with a general dental practitioner. According to Hospital Episode Statistics, approximately 0·08% of visits to MEDs are for dental‐related problems in the UK ; however, a much higher proportion is seen in the United States (1·65%), approximating to 2·1 million attendances per year.…”
Section: Introductionmentioning
confidence: 99%
“…Over the 6-week period there was a relatively equal split of patient gender attending the UDCC, this is in contrast with typical patient demographics accessing emergency dental care whereby the patient population is predominantly male (12)(13)(14). This change in demographic could reflect the change in service provision, whereby female patients who were more likely to be registered with a GDP in this cohort, and who are more likely to seek care at an early stage (15,16) started to present to the UDCC rather than primary care.…”
Section: Discussionmentioning
confidence: 92%
“…A higher prevalence of suicide ideation was observed among those with both TMD and lower EQ‐PD utility. In a study of adult patients attending emergency services for dental problems, Currie and colleagues reported that EQ‐5D scores were low compared to population norms . Among approximately 900 Han Chinese older adults, Gao et al .…”
Section: Introductionmentioning
confidence: 99%